Me and my house : James Baldwin's last decade in France - Zaborowska, Magdalena J. (Duke University Press, 2018)
"The last sixteen years of James Baldwin's life (1971-87) unfolded in a village in the South of France, in a sprawling house nicknamed 'Chez Baldwin.' In Me and My House Magdalena J. Zaborowska employs Baldwin's home space as a lens through which to expand his biography and explore the politics and poetics of blackness, queerness, and domesticity in his complex and underappreciated later works. Zaborowska shows how the themes of dwelling and black queer male sexuality in The Welcome Table, Just above My Head, and If Beale Street Could Talk directly stem from Chez Baldwin's influence on the writer. The house was partially torn down in 2014. Accessible, heavily illustrated, and drawing on interviews with Baldwin's friends and lovers, unpublished letters, and manuscripts, Me and My House offers new insights into Baldwin's life, writing, and relationships, making it essential reading for all students, scholars, and fans of Baldwin."--